The roles of language in CLIL - Llinares, Ana, 1968-; Morton, Tom, 1958-; Whittaker, Rachel (Cambridge : Cambridge University Press, 2012)
'An examination of how language functions in CLIL, based on a corpus of classroom interactions. Drawing on their wide experience as CLIL educators and researchers, the authors explore data collected in real CLIL classrooms from two interrelated perspectives: the CLIL classroom as an interactional context for developing language and content, and the genres and registers through which the meanings of the different academic subjects are enacted. From the analysis of this corpus of data, the authors provide a rich description of how CLIL students' language works and may be expected to develop. Also available separately as a paperback'--
'Drawing on their wide experience as CLIL educators and researchers, the authors explore data collected in real CLIL classrooms from two interrelated perspectives: the CLIL classroom as an interactional context for developing language and content, and the genres and registers through which the meanings of the different academic subjects are enacted. From the analysis of this corpus of data, the authors provide a rich description of how CLIL students' language works and may be expected to develop'--
Includes bibliographical references and index.
Keywords: Language and languages -- Study and teaching